Indirect Spectrophotometric Determination of Oxymetazoline Hydrochloride in Pharmaceutical Formulation Using Fluorophotometric Method - Saleem, Mohammed S.; Othman, Ikram K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research involves an indirect Fluorophotometric method for the determination of microgram amount of oxymetazoline hydrochloride in the concentration range 0.1-5.0 g/ml. The method is based on the oxidation of the drug by cerium sulphate solution which is acidic medium where Ce IV is reduced to Ce III which can be excited at 259 nm to give an emitted light at 377 nm which  is directly proportional to the concentration of Ce III which is equivalent to Ce IV that is needed to oxidize the studied drug. The average recovery of the method is 100.19% and relative standard deviation (RSD) < 0.37% . The method have been successfully applied to the determination of the studied drug in its pure and pharmaceutical preparations and it was found that the results obtained are agree favorably with certified values of pharmaceutical preparations and also with  result obtained by standard addition method.